A political world within the parameters of SABC politics - Susan Booysen (Communicare)
Political events are crucial in the political resocialisation of the youth. In this article the impact of the political unrest in the mid-1980s on the political consciousness of the Afrikaner student youth is investigated. Through a panel study of students of the Rand Afrikaans University in Johannesburg, South Africa, trends in exposure to political events were established. Exposure occurs through direct political participation, political discourse or through the mass media. The important role of the mass media for exposure of these youths is illuminated. Attention is also focused on which media are utilised for obtaining political information. The political implications of this exposure are considered. A political world within the parameters of SABC politics: the case of Afrikaner students.